If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4b + 4) + (17b + -3) = 0 Reorder the terms: -4(4 + 4b) + (17b + -3) = 0 (4 * -4 + 4b * -4) + (17b + -3) = 0 (-16 + -16b) + (17b + -3) = 0 Reorder the terms: -16 + -16b + (-3 + 17b) = 0 Remove parenthesis around (-3 + 17b) -16 + -16b + -3 + 17b = 0 Reorder the terms: -16 + -3 + -16b + 17b = 0 Combine like terms: -16 + -3 = -19 -19 + -16b + 17b = 0 Combine like terms: -16b + 17b = 1b -19 + 1b = 0 Solving -19 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 1b = 0 + 19 Combine like terms: -19 + 19 = 0 0 + 1b = 0 + 19 1b = 0 + 19 Combine like terms: 0 + 19 = 19 1b = 19 Divide each side by '1'. b = 19 Simplifying b = 19
| -90z-0.9=-100z+1.5 | | 90z-0.9=-100z+1.5 | | -7(5y+7)= | | 2.1q-5.2-3.5q=-2.4q-4.1 | | x^3-5x^2-11x-3=0 | | 4m+8=-8 | | 190=L+9(w) | | 5t-t-8=3t-6 | | 8z+z=8z+5 | | 42=2(l)(w) | | 2(2x+40)2x=680 | | 2(x+40)+x=680 | | 6+2(3m-4)-16m= | | 2(x+40)+2x=680 | | 5t-t-8=3t+6 | | -16+4=-2(x+3) | | -16+4=-2(2x+3) | | 1-3(y-5)=-5(y-2) | | 5(x-4)+6=2x+3(-4+x) | | 6.1x-3+x-1.9= | | r-8.5=-8.1 | | -2(7x-7)+1=-14x+15 | | (7y+6)-(2+6y)=9 | | (x-1)(x-4)(x-6)+(-2)(-5)(-3)+(-3)(-2)(-5)-(-2)(-2)(x-6)-(x-1)(-5)(-5)-(-3)(x-4)(-3)=0 | | pe=9c | | 4y+4y=7y-5 | | [5-2(5-4)]= | | (w+23)+(4w+7)=18 | | 6x+2+4x+9=9x+3 | | 4y=7-5x | | -2x-(7x+1)= | | x^3+x^2-3x=0 |